Review of the Centers for Disease Control and Prevention's smallpox vaccination program implementation. (The National Academies Press, 2003)
In this report, the committee addresses several important issues: the vaccination program's need for evaluation (including program safety) and clearly defined objectives; a needed emphasis on defining preparedness against smallpox attack; CDC's communications plans; CDC's training and education efforts; the systems for monitoring the safety of the vaccine; the need for a compensation program; and matters of resource allocation.